2018
DOI: 10.1002/bbb.1892
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable power generation from wastewater sources using Microbial Fuel Cell

Abstract: Microbial fuel‐cell performance depends primarily on five factors: the nature of the electrodes, pH, concentration, temperature, and period of operation. The present work describes work on optimization that has resulted in improved system performance of processes for energy recovery from wastewater by addressing these five parameters. This optimization is related to Monod kinetics, which forms the basis for microbial growth and substrate depletion rate. A difference in energy recovery from wastewater sources h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 55 publications
(129 reference statements)
0
11
0
Order By: Relevance
“…In certain areas where electricity reaches but the light is so dim that it is next to nonexistent, levels of satisfaction are again low (Herington et al 2017). The industry working in this area should focus on cost‐effective lighting solutions that ensure clean fuel as part of sustainable development (Kapoor et al 2017; Bose et al 2018a, 2018b). Off‐grid solar is lower in cost compared to the price of kerosene when the time factor is considered, as the payback for solar PV‐based energy generation systems is shorter.…”
Section: Remote Communitiesmentioning
confidence: 99%
“…In certain areas where electricity reaches but the light is so dim that it is next to nonexistent, levels of satisfaction are again low (Herington et al 2017). The industry working in this area should focus on cost‐effective lighting solutions that ensure clean fuel as part of sustainable development (Kapoor et al 2017; Bose et al 2018a, 2018b). Off‐grid solar is lower in cost compared to the price of kerosene when the time factor is considered, as the payback for solar PV‐based energy generation systems is shorter.…”
Section: Remote Communitiesmentioning
confidence: 99%
“…For sewage, the major components that need to be treated before discharge include dissolved solids, suspended solids, alkalinity (as CO 3 1− ), sulfate (as SO 4 2− ), nitrates (NO 3 − ), phosphates (PO 4 3− ) with organic loads of sodium (Na 2+ ), calcium (Ca +2 ), magnesium (Mg), potassium (K + ), chlorine (Cl − ), ammonia (NH 3 1+ ), and trace quantities of manganese, copper, and zinc, all of which contributes to mg-COD/L of wastewater. The primary goal of MFCs is to reduce the COD followed by the energy recovery as bioelectricity.…”
Section: Comparative Analysismentioning
confidence: 99%
“…Ultraviolet-visible spectrophotometry of untreated wastewater (here shown as WW) and wastewater after 1 week of operation of MFC, the pattern shows absorbance has increased from an initial 0.5 (brown shift) to 0.6 (blue shift), thereby removing mass concentration of contaminants in the process, the ideal absorbance for a standard solution (DM water) is also shown to peak at 1 [Colour figure can be viewed at wileyonlinelibrary.com] MFCs is to reduce the COD followed by the energy recovery as bioelectricity. For sewage, the major components that need to be treated before discharge include dissolved solids, suspended solids, alkalinity (as CO 3 1− ), sulfate (as SO 4 2− ), nitrates (NO 3 − ), phosphates (PO 4 3− ) with organic loads of sodium (Na 2+ ), calcium (Ca +2 ), magnesium (Mg), potassium (K + ), chlorine (Cl − ), ammonia (NH 3 1+ ), and trace quantities of manganese, copper, and zinc, all of which contributes to mg-COD/L of wastewater. 33 Studies have shown the various types of pathogens present in the wastewater at thermophilic temperatures (20-30°C) usually include viruses (Enteroviruses), bacteria (Salmonella spp., Vibrio cholerae, Shigella spp., and Fecal coliforms), protozoa (Entamoeba histolytica cysts), and Helminths.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…One appealing solution is the use of waste to produce electricity. 5,6 Globally, huge money is spent treating large quantities of wastewater each year, consuming considerable amounts of energy. This wastewater could thus serve as a renewable resource, saving significant amounts of energy and money in their toxicity removal and treatment.…”
Section: Introductionmentioning
confidence: 99%